Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.isprsjprs.2020.04.011
|View full text |Cite
|
Sign up to set email alerts
|

A multi-plot assessment of vegetation structure using a micro-unmanned aerial system (UAS) in a semi-arid savanna environment

Abstract: offered throughout this process. When I expressed interest in field work as a career goal, I was offered an opportunity to work in the field as part of a collaborative research effort and they shared their expertise. Both made themselves available to workshop methodological issues and academic decisions in the context of my work and larger goals. Through their mentorship, and that of the Geography Department as a whole, I have achieved well beyond what I initially intended as a student and am encouraged to car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 81 publications
(83 reference statements)
1
13
0
Order By: Relevance
“…Despite significantly lower point cloud densities, NIR point clouds produced in that study consistently showed better representation of the canopy structure than denser RGB point clouds, and the same finding was noted elsewhere [43]. For more details regarding the processing parameters, please see [37].…”
Section: Field Data and Uas-derived Canopy Height Modelsupporting
confidence: 71%
See 2 more Smart Citations
“…Despite significantly lower point cloud densities, NIR point clouds produced in that study consistently showed better representation of the canopy structure than denser RGB point clouds, and the same finding was noted elsewhere [43]. For more details regarding the processing parameters, please see [37].…”
Section: Field Data and Uas-derived Canopy Height Modelsupporting
confidence: 71%
“…To produce canopy height models (CHMs), we subtracted the DTM from the corresponding DSM, which included the above-ground vegetation structure as generated by the SfM-MVS algorithm. We chose to use NIR-derived CHMs exclusively for this analysis as previous work determined that increased spectral detail in vegetation improves canopy height estimates even at the expense of coarser spatial resolution [37]. Despite significantly lower point cloud densities, NIR point clouds produced in that study consistently showed better representation of the canopy structure than denser RGB point clouds, and the same finding was noted elsewhere [43].…”
Section: Field Data and Uas-derived Canopy Height Modelmentioning
confidence: 74%
See 1 more Smart Citation
“…We subsetted each dataset using .exif data on height of captured image and geolocation tags to calculate the width of each image footprint (via the exifr package in R) [37]. We then used a distance of seven meters to create a buffered polygon of all the GPS point locations of each photo and used the convex hull setting in the Minimum Bounding tool in ArcPy [38]. The resulting polygon indicates the area of the flight footprint with substantive image overlap and thereby excludes distorted margins of orthomosaics [38].…”
Section: Image Subsettingmentioning
confidence: 99%
“…We then used a distance of seven meters to create a buffered polygon of all the GPS point locations of each photo and used the convex hull setting in the Minimum Bounding tool in ArcPy [38]. The resulting polygon indicates the area of the flight footprint with substantive image overlap and thereby excludes distorted margins of orthomosaics [38].…”
Section: Image Subsettingmentioning
confidence: 99%